Improving Vocabulary Skills Through Project-Based Learning With Digital Picture Media for Children With Speech Disorders in Third Grade of Elementary School - Anggraini, Gustina; Suparno, Suparno (Journal of Management Economic and Financial, 2025)
Children with speech disorders experience difficulties in understanding and using vocabulary, which affects their academic performance and social skills. Conventional verbal-based learning approaches are often ineffective, thus requiring strategies that are more visual, concrete, and interactive. This study aims to improve the vocabulary skills of children with speech disorders using digital image media based on Project Based Learning (PjBL). This research employed a Classroom Action Research (CAR) method conducted in three cycles in 3rd Class of YPPSB 3 Elementary School, North Sangatta. The subjects consisted of four students identified as having speech disorders. Data were collected through observation, learning outcome tests (pretest and posttest), and documentation of learning activities. The result of the study shows a significant improvement in students' vocabulary abilities. The average pre-action score of 33.37% increased to 53.75% in cycle I, 67.5% in cycle II, and reached 75% in cycle III. Three out of four students (75%) achieved scores up to 98.75% and categorized as "Developing Very Good" (BSB), while one student was categorized as "Developing Accordingly" (BSH). This improvement covered receptive (listening, understanding) and productive (speaking, retelling) aspects. Digital image media provided concrete visual stimuli, while the PjBL approach encouraged student engagement and collaboration. The combination proved effective in creating an enjoyable, contextual, and inclusive learning experience for children with speech disorders.